PEMETAAN SEKOLAH DI TANAH DATAR (SEBUAH KAJIAN DAN REKOMENDASI) - Sirajul Munir (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2008)
Data provider as the main input in planning and formulating policies is a very important thing in education field. Consequently, school mapping, a micro or regional educational planning approach to figure out the efficiency and effectiveness of education process, is urgently needed. From school mapping conducted in Tanah Datar, it was found that: (1) significant overloaded of elementary (SD) and junior high school (SMP) teachers, (2) the educational qualification of many teachers in those levels are still bachelor (diploma) holders, (3) teachers are not well distributed.Kata Kunci: pemetaan sekolah, regrouping, multi-grade, kelebihan guru, dan kualifikasi